A semantic broadcasting method for the exchange of encoded texts between different XML schemas - Poulos, Marios (2021)
In this paper, we introduce a novel method, based on specific frequency segmentation, for the exchange of encoded texts between different XML schemas. In this process, we encode the text part of each element of the Dublin Core using a signal processing technique so that every text element broadcasts an audio signal in a unique frequency. In this way, every schema based on the XML language can exchange textual data. This method may be used in order to interchange different philosophies of the XML Schema and may also be used as a solution to the general problem of interoperability. More specifically, this method may be applied to TV metadata and the broadcasting services of automated libraries.